Kinetics of hydroformylation of 1-decene using carbon-supported ossified HRh(CO)(TPPTS)(3) catalyst - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2019)
The kinetics of hydroformylation of 1-decene has been investigated using a carbon-supported ossified HRh(CO)(TPPTS)(3)/Ba catalyst in a temperature range of 343-363 K. The effect of concentration of 1-decene, catalyst loading, partial pressure of H-2 and CO, and stirring speed on the reaction rate has been investigated. A first-order dependence was observed for catalyst concentration and hydrogen partial pressure. The rate showed a typical case of substrate inhibition for high 1-decene concentration. The rate varied with a linear dependence on P-CO up to a CO partial pressure of 5-6 MPa in contrast to the general trends; for most of the rhodium-phosphine catalyzed hydroformylation reactions, severe inhibition of rate is observed with an increase in CO pressure. A rate equation has been proposed, which was found to be in good agreement with the observed rate data within the limit of experimental errors. The kinetic parameters and activation energy values have been reported.
Keywords: 1-decene; Hydroformylation; kinetics; ossification; supported ossified

Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite

Kinetics of 1-decene hydroformylation in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of a cosolvent - Pagar, Nitin S.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2021)
The kinetics of hydroformylation of 1-decene has been studied in an aqueous biphasic medium using a water-soluble Rh-sulfoxantphos catalyst in the presence of N-methyl pyrrolidone as a cosolvent at 383-403 K. The rate was found to be first order, with concentrations of catalyst and olefin and partial order, with concentrations of hydrogen in the liquid phase. The plot of rate versus excess ligand and CO concentrations passed through maxima, indicating negative order dependence at higher concentrations. These trends have been interpreted based on the established hydroformylation mechanism. High selectivity towards the linear aldehyde was maintained (n: iso ratio > 30). An empirical rate equation has been proposed which was found to be in good agreement with the observed rate data within the experimental error. The activation energy was evaluated to be 74.76 kJ/mol.
Keywords: 1‐ aqueous‐ biphasic; cosolvent; decene; Hydroformylation; kinetics; rh‐ sulfoxantphos